Is it safe and efficacious to remove central lines in pediatric bone marrow transplant patients with platelets less than 20, 000/μl?. Issue 1 (15th January 2022) - Marwah, Priya; Ramprakash, Stalin; Prasad T R, Sai; Gizhlaryan, Mane; Trivedi, Deepa; Shah, Vaibhav; Chitaliya, Amit; Elizabeth, Sandeep; Agarwal, Rajat Kumar; Dhanya, Rakesh; Faulkner, Lawrence
Abstract: Background: Patients with tunneled central venous lines (CVL) may develop bloodstream infections which at times are difficult to control without line removal. Concomitant severe thrombocytopenia with platelet transfusion refractoriness is often considered a major contraindication to any procedure involving a major blood vessel. There is very little literature on the clinical risks of tunneled central line removal in febrile pancytopenia patients. Procedure: We analyzed complications and outcomes in all our patients, a total of 52, who underwent CVL removal with platelets <20, 000/μl. Results: CVL removal was done on a median day of 17.5 with 47 of the 52 patients never having achieved platelets engraftment prior to line removal. No bleeding episodes or unplanned transfusions could be associated with CVL removal. No other complications were also reported. All patients had time to hemostasis within 5 min of catheter removal. Removal of CVL under local anesthesia remained complication‐free even at platelet counts less than 20, 000/ul. A total of 31 patients were febrile at the time of CVL removal, of which 17 became afebrile within 2 days. We found no difference in defervescence when comparing those whose antibiotic therapy was changed/escalated versus those in whom it was not. Conclusion: Our findings suggest that central lines can be safely removed with platelet counts less than 20, 000/ul and that this may result in enhanced bloodstream infection control. This might be particularly relevant to neutropenic patients in this day and age of multidrug‐resistant organism emergence and paucity of new effective antibiotics.